2018
DOI: 10.1007/s11248-018-0096-8
|View full text |Cite
|
Sign up to set email alerts
|

In vivo epigenome editing and transcriptional modulation using CRISPR technology

Abstract: The rapid advancement of CRISPR technology has enabled targeted epigenome editing and transcriptional modulation in the native chromatin context. However, only a few studies have reported the successful editing of the epigenome in adult animals in contrast to the rapidly growing number of in vivo genome editing over the past few years. In this review, we discuss the challenges facing in vivo epigenome editing and new strategies to overcome the huddles. The biggest challenge has been the difficulty in packaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 117 publications
0
15
0
Order By: Relevance
“…Transcriptional modulation offers several advantages over genome editing, such as restoring normal gene expression without inducing DNA damage and off-target mutagenesis. With the exception of gene knockout, 39 no study yet has reported the use of an all-in-one AAV system for the delivery of CRISPR fusion protein and its sgRNA into the adult mouse brain 40 . To our knowledge, the existing strategies to enable transcriptional modulation in vivo were based on the use of a dual-vector AAV system, 41 a split dCas9 AAV system,42, 43 or Cre-inducible dCas9-expressing mice 44, 45, 46.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptional modulation offers several advantages over genome editing, such as restoring normal gene expression without inducing DNA damage and off-target mutagenesis. With the exception of gene knockout, 39 no study yet has reported the use of an all-in-one AAV system for the delivery of CRISPR fusion protein and its sgRNA into the adult mouse brain 40 . To our knowledge, the existing strategies to enable transcriptional modulation in vivo were based on the use of a dual-vector AAV system, 41 a split dCas9 AAV system,42, 43 or Cre-inducible dCas9-expressing mice 44, 45, 46.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, catalytically inactive Cas9 has been fused to various epigenetic effectors such as the catalytic core of the human acetyltransferase p300 which catalyzes acetylation of histone H3 lysine 27 ( Hilton et al, 2015 ), histone demethylase ( Kearns et al, 2015 ), histone deacetylase (HDAC) ( Kwon et al, 2017 ) and many others (reviewed in Lau and Suh, 2018 ).…”
Section: Transcriptional Modulation and Epigenome Editingmentioning
confidence: 99%
“…DNA methylation is initiated by DNA methyltransferase (DNMT), so controlling DNMT activity should in turn control DNA methylation. By fusing dCas9 to a catalytic domain of DNMT, such as DNMT3 or MQ3, CRISPR/Cas systems have successfully targeted methylation to specific sites in both plants and animals ( Liu et al, 2016 ; Vojta et al, 2016 ; Lau and Suh, 2018 ). By fusing dCas to a demethylation enzyme, such as a ten-eleven translocation (TET) family member, the CRISPR/dCas system may also be used to remove methyl groups from specific DNA sequences, initiating increased expression of the target gene.…”
Section: Crispr/cas Precision Genome Editingmentioning
confidence: 99%